An Analysis of Code Mixing Used by Sacha Stevenson’s Conversation “House Tour” - Luh Gede Kumala, Dewi; I Dewa Ayu Devi Maharani Santika (ELYSIAN JOURNAL : English Literature, Linguistics and Translation Studies, 2025)
This study delves into code mixing in the conversation "House Tour" by Sacha Stevenson, examining its types, functions, and motivations. The primary data source for this study is derived from the video content of Sacha Stevenson, particularly focusing on the conversation titled "House Tour." A total of videos from her YouTube channel were selected for analysis. In addition to linguistic analysis, this study also delves into the sociolinguistic and pragmatic factors influencing code mixing. The result of this research is, the code mixing observed in Sacha Stevenson's conversation highlights the sophisticated navigational skills of bilingual speakers. The adaptability showcased through internal code switching reveals how individuals draw from their linguistic arsenal to effectively communicate intricate ideas.